2019
DOI: 10.2147/prbm.s159260
|View full text |Cite
|
Sign up to set email alerts
|

<p>Conceptualizing anhedonias and implications for depression treatments</p>

Abstract: Anhedonia has been implicated as a core symptom of depression and schizophrenia, and studying anhedonia has yielded a wide array of important findings aiding the understanding and identification of psychological disorders. However, anhedonia is a complex and multifaceted construct; indeed, the term anhedonia has been defined in psychological and psychiatric research as many different concepts, a number of which are theoretically and methodologically independent of one another. In this review alone, we discuss … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
34
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 68 publications
4
34
0
Order By: Relevance
“…Assessment of anhedonia as such could then lead to a better understanding of the depressed patient and (in the end) better outcome. This better understanding in general could be as (or even more) important than the different phases of the pleasure cycle as specific targets for biological or psychotherapeutic interventions [70].…”
Section: Discussionmentioning
confidence: 99%
“…Assessment of anhedonia as such could then lead to a better understanding of the depressed patient and (in the end) better outcome. This better understanding in general could be as (or even more) important than the different phases of the pleasure cycle as specific targets for biological or psychotherapeutic interventions [70].…”
Section: Discussionmentioning
confidence: 99%
“…Lastly, Dunn and colleagues' (2019) new Augmented Depression Therapy (ADepT) that addresses why depressed individuals are hesitant to approach positivity has recently shown to be an efficacious treatment for patients who did not initially respond traditional CBT, with stronger changes in dampening appraisals about prospective positivity for individuals who completed ADepT versus CBT (for a review of other novel depression treatments, see Winer et al, 2019). Taken together, recent clinical research has emphasized a need for focusing on the upregulation of positive affect in both anxiety and depression, and new treatments are highlighting ways to increase those outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…For example, hallmark treatments for depression have often focused on reducing negative affect and/or assuming the depressed patient suffers from an inability to experience positive affect (Beck & Bredemeier, 2016). Further, current nosology also simply emphasizes a “markedly diminished interest” in activities (American Psychiatric Association, 2013), possibly conflating distinct experiences that can result in this loss of interest (Winer et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Negative schizotypy was speci cally associated with increases in trait social and state anhedonia whereas disorganized schizotypy and affective symptoms were uniquely associated with increases in depressive anhedonia. This nding is supported by research showing that anhedonia is heterogeneous across psychiatric disorders, depending on which parts of the pleasure networks are most affected [14,36]. Indeed, more trait-like expression of social anhedonia and physical-related hedonic de cits emerge more robustly in relation to schizophrenia-spectrum symptoms whereas recent increases in anhedonia are predictive of symptoms that are more indicative of depression and suicidal ideation [9,10,13,21].…”
Section: Discussionmentioning
confidence: 84%
“…Previous studies have suggested that recent changes in anhedonia were an important predictor of negative symptoms, depression and suicidal ideation [7][8][9][10][11][12][13]. It suggested recent changes in anhedonia may be uniquely predictive of key elements of psychopathology [14,15]. These nding have suggested that the distinction between trait, state and recent changes in anhedonia is of crucial importance when studying anhedonia, and recent changes in anhedonia, may be a stronger predictor of psychological disorders than trait and state anhedonia.…”
Section: Introductionmentioning
confidence: 98%